Leaf Spot Disease Development and Its Effect on Yield of Essential Oil-Producing Hemp Cultivars in Kentucky - Munir, Misbakhul (Plant disease, 2024)
Leaf spot diseases are common on field hemp, causing defoliation, and blighting. The most prevalent leaf spot diseases of hemp in Kentucky are Bipolaris leaf spot (Bipolaris gigantea), Cercospora leaf spot (Cercospora flagellaris), and Septoria leaf spot (Septoria cannabis). In this study, disease progression, cultivar susceptibility, and yield loss were examined using cultivars from four relatedness groups at two locations and in two growing seasons. Septoria leaf spot was the first leaf spot disease to be observed in the field, followed by Bipolaris leaf spot. Both diseases reduced canopy density. Cercospora leaf spot developed in the late reproductive stages as harvest approached. A wide range of susceptibility was documented, suggesting genetic variability across cultivars. Trump group cultivars were the most susceptible, while Otto II group cultivars were the least susceptible. Most importantly, leaf spot diseases had minimal influence on floral biomass and no effect on CBD yield, suggesting that, regardless of disease severity, leaf spot diseases may seldom warrant management. While the importance of foliar disease and corresponding yield loss can shift over time, variation in disease progress among leaf spot diseases and susceptibility of hemp cultivars documented in this study suggest potential disease management through cultural practices such as cultivar and planting date selections